1957
DOI: 10.1021/ac60130a037
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Panthenol and Pantothenates in Multivitamin Preparations

Abstract: of the anion exchange resin in tertbutyl alcohol.By paper strip chromatography as described by Stark and coworkers (9), with an authentic sample of malic acid for comparison, it was shown that the fermentation containing 30% weak acids (Table III) contained only one weak acid which had the same R¡ value as a malic acid. This finding confirmed a statement by Lemjahov (6) that fumaria acid fermentations often contain malic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…A standard deviation (SD) of 0.26 was obtained in 10 replicate experiments, when thc specific rotation was determined at 589 nm. The precision of the spectropolarimetric technique employed in the present study compares favorably to the precision obtained by Schmall and Wollish (7) with the colorimetric methods. Colorimetry-Calcium pantothenate was determined according to the method of Schmall and Wollish (7), using ninhydrin as the coloring reagent.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…A standard deviation (SD) of 0.26 was obtained in 10 replicate experiments, when thc specific rotation was determined at 589 nm. The precision of the spectropolarimetric technique employed in the present study compares favorably to the precision obtained by Schmall and Wollish (7) with the colorimetric methods. Colorimetry-Calcium pantothenate was determined according to the method of Schmall and Wollish (7), using ninhydrin as the coloring reagent.…”
supporting
confidence: 80%
“…The precision of the spectropolarimetric technique employed in the present study compares favorably to the precision obtained by Schmall and Wollish (7) with the colorimetric methods. Colorimetry-Calcium pantothenate was determined according to the method of Schmall and Wollish (7), using ninhydrin as the coloring reagent. The procedure and reagents, with the exception of the preliminary column chromatography, are exactly as described in Rqferrrse 7.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The analytical data were then evaluated by a method similar to Hubaux and Vos (2) to determine a statistically based limit of detection for this method. This technique is similar to the statistical methods defined by Parsons (3) and Currie (4). polymer packing2.…”
Section: Results a N D Discussionmentioning
confidence: 97%
“…A number of satisfactory methods are available for the identification and determination of the pantothenates and pantothenyl alcohol (panthenol) (1)(2)(3)(4)(5)(6)(7). However, previous reports (8)(9)(10)(11)(12)(13)(14)(15) havc shown that some of the water-soluble vitamins are anienable to GLC, thus suggesting that panthenol, pantothenic acid, and the pantothenic acid salts could also be determined by this technique.…”
mentioning
confidence: 99%